Excitation of the 15.1 MeV resonance of C-12 by channeling radiation - Kalinin B. N.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Stibunov V. N. Victor Nikolaevich; Vnukov I. E. (1993, 1993)
Title screen